A Study to Assess the Attitude towards Application of Evidence-based Education System among Post-graduate Students of Sumandeep Vidyapeeth - Patel, Bhoomika; V. , Suresh; Patel, Bhavisha; Madhavi, Vaghasiya; Janki, Patel; Khilan, Patel (International Journal of Psychosocial Rehabilitation, 2020)
Background: Evidence-based education (EBE) is the use of well-structured scientific studies to find out which education methods work best. It consists of evidence-based teaching, evidence-based learning, and evidence-based clinical practices too. Furthermore, it’s also considered a keystone for the healthcare system. Further attention and care are needed on strategies that not only focus on issues or problems that occur but also have the capacity to change and the competence to face the challenge of providing such EBP in education and clinical aspects.Objectives: Descriptive study to assess the attitude of postgraduate students towards the application of the evidence-based education system and to find out the association of it with selected demographic variables.Materials and Methods: Quantitative research approach with descriptive design used. The convenience sampling technique was used to select 252 postgraduate students of Sumandeep Vidyapeeth, and data collection was done with a self-structured attitude scale. Data was analyzed with descriptive and inferential statistics.Result: It revealed that 84.5% of PG students have a positive attitude and 15.5% of students have a negative attitude toward EBES. There is an association of the attitude with some of the selected demographic variables, such as year of study and course of study, at the 0.05 level of significance.Conclusion: The study revealed that most of the students have a positive attitude toward EBES. First-year students have a more positive attitude than other students.